Lucumi Divination, the Mythic World and the Management of Misfortune - Brandon, George (Anthropologica, 2012)
This paper examines Lucumi healing practices in re lation to anthropological understandings of how symbolic heal ing works. This essay focuses upon divination because so much that is fundamental to the process of symbolic healing in Lucumi religion occurs during divination. After tracing the evolution of Lucumi Orisha worship, I describe Lucumi etiological theory, its basic categories of misfortune and how interaction between cowrie shell diviners and their clients sets people on the road to healing. After this I compare Lucumi divination practices with those of two other healer types who also use cowries in divination.